Cardiac diagnostic tests a guide for nurses - VanRiper, Sharon; VanRiper, John (W.B. Saunders, 1997)
Cardiac Diagnostic Tests: A Guide for Nurses places the key diagnostic knowledge you need at your fingertips. Inside, you'll find detailed descriptions of each type of diagnostic test - explaining why the test is chosen, how it is performed, how the results are interpreted, and what care is required before, during, and after the test.